Penguatan Verbal dan Nonverbal dalam Pembelajaran Bahasa Indonesia Siswa Kelas XII SMA Negeri 11 Makassar (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the form of verbal and nonverbal reinforcement in Indonesian language learning for students of class XII SMA Negeri 11 Makassar. The approach in this research uses a descriptive qualitative approach, the data source is the XII grade Indonesian language teacher. Data collection techniques in this research are recording techniques and note-taking techniques. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results showed that the grade XII Indonesian language teacher had implemented verbal form of reinforcement in Indonesian language learning and nonverbal form in Indonesian language learning. The reinforcement given is quite varied, but the diction needs to be developed again.